E-Commerce and Fintech Integration: Future Solutions for Digital Commerce - Riska Ardila Hasanah; Dea Putri Ananda; Nurulia Ramadhani; M. Abdul Ghapur (Penerbit Hellow Pustaka, 2024)
The flow of economic digitalization, including Fintech, has enormous potential to encourage more efficient allocation of economic resources and encourage increased productivity and provide greater benefits for customers. Fintech is able to overcome all problems in transactions because of its advantages in terms of regulations, innovation and service development facilities. Electronic commerce (e-commerce) is an online channel that can be reached by individuals via computers, used by entrepreneurs to conduct business, and used by consumers to obtain information using computers. The type of research used in this research is using a qualitative descriptive type, namely research in the form of words, images and not numbers in collecting data with the aim of describing events obtained based on data in the field. The use of fintech and e-commerce has provided easy accessibility for consumers in financial transactions. For example, digital payment services allow consumers to pay bills, transfer money, or shop quickly and easily through apps on their phones. Superior user experience should also be a focus in this strategy.